User's guide to sample size estimation in diagnostic accuracy studies - AKOĞLU, HALDUN (My University, 2022)
© 2022 Emergency Medicine Association of Turkey. All rights reserved.Sample size estimation is an overlooked concept and rarely reported in diagnostic accuracy studies, primarily because of the lack of information of clinical researchers on when and how they should estimate sample size. In this review, readers will find sample size estimation procedures for diagnostic tests with dichotomized outcomes, explained by clinically relevant examples in detail. We hope, with the help of practical tables and a free online calculator (https://turkjemergmed.com/calculator), researchers can estimate accurate sample sizes without a need to calculate from equations, and use this review as a practical guide to estimating sample size in diagnostic accuracy studies.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Yoğun Bakım; Cerrahi Tıp Bilimleri; Acil Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Intensive Care; Surgery Medicine Sciences; Emergency Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; YOĞUN BAKIM; ACİL TIP; Clinical Medicine (MED); CLINICAL MEDICINE; CRITICAL CARE MEDICINE; EMERGENCY MEDICINE; Yoğun Bakım Tıbbı; Critical Care and Intensive Care Medicine; Calculator; diagnostic accuracy; online; sample size; sensitivity; specificity